Key factors affecting the success of business operations of Turkish firms operating in Bulgaria -An emerging market perspective - Halibryam, Zayde (My University, 2010)
The main objective of this research is to find out the key factors assuring success for Turkish business organizations operating in the Bulgarian market. Describing the characteristics of these firms, identifying the factors affecting their market choice, and defining the most preferred mode of entry are also between the objectives of the study. Turkey and Bulgaria are neighbours and important trade partners. Both of them are Emerging Markets, which are described by some authors as major growth opportunity in the evolving world economic order (Arnold and Quelch, 1998). Therefore it is very important to investigate the success factors from the EM perspective. The study includes the review of literature and a field survey. For the field survey, a questionnaire was e-mailed to the Turkish firms operating in Bulgarian market. The findings of the research show that the majority of the firms contacted are small and medium sized firms which prefer the strategy of direct exporting in their operations in Bulgaria. The results of the survey emphasize that the Turkish firms operating in Bulgaria see as a most important success factors implementing competitive pricing strategies and meeting the needs of the customers. Quality in products, and production and innovativeness in products and production technologies are also between important success factors.

Bu araştırmanın temel amacı Bulgaristan pazarında faaliyet gösteren Türk işletmelerinin başarısını sağlayan temel faktörleri tespit etmektir. Bu şirketlerin özelliklerini tanımlamak, pazar seçim süreçlerinde etkili olan faktörleri belirlemek, en çok tercih ettikleri pazara giriş stratejisini tanımlamak çalışmanın diğer amaçları arasında yer almaktadır. Türkiye ve Bulgaristan hem önemli ticari partner hem de komşular. İkisi de, bazı yazarlar tarafından Gelişen dünya ekonomik düzeninde temel büyüme fırsatı şeklinde tarif edilen Yükselen Pazarlar arasında yer almaktadırlar. (Arnold and Quelch, 1998). Bu yüzden başarı faktörlerinin Yükselen Pazarlar perspektifinden incelenmesi çok önemlidir. Çalışma, literatür taraması ve saha araştırması içermektedir. Saha araştırmasında, Bulgaristan’da faaliyet gösteren Türk şirketlerine e-mail yoluyla bir anket gönderilmiştir. Araştırmanın sonuçları, anketi yanıtlayan firmaların küçük ve ya orta ölçekli olan ve doğrudan ihracat stratejisini tercih eden şirketler olduğunu göstermektedir. İncelemenin sonuçları, Bulgaristan’da faaliyet gösteren Türk şirketlerinin en önemli başarı faktörü olarak, rekabetçi fiyat stratejileri uygulamayı ve müşterilerin ihtiyaçlarını karşılamayı gördüklerini vurgulamaktadır. Ürün ve üretimde kalite, ürün ve üretim teknolojilerinde inovasyon da başarı faktörleri arasında yer almaktadır.
Keywords: Pazarlama; Üretim Yönetimi